2011
DOI: 10.1021/bi200815e
|View full text |Cite
|
Sign up to set email alerts
|

The Glutamine Side Chain at Position 91 on the β5a−β5b Loop of Human Immunodeficiency Virus Type 1 Reverse Transcriptase Is Required for Stabilizing the dNTP Binding Pocket

Abstract: Earlier, we postulated that Gln91 of HIV-1 RT stabilizes the side chain of Tyr183 via hydrogen bonding interaction between O(H) of Tyr183 and CO of Q91 (Harris et al., BIOCHEMISTRY 37: 9630, 1998). To test this hypothesis, we generated mutant derivatives of Gln91 and analyzed their biochemical properties. The efficiency of reverse transcription was severely impaired by nonconservative substitution from Gln→Ala, while conservative substitution from Gln to Asn resulted in approximately 70% loss of activity, a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…This approach would allow "dissecting" between the clamp function and all other RT activities. Therefore, one of the suspected residues, Gln91, was not tested here, since it was already found that the Q91N HIV-1 RT mutation leads to a loss of Ͼ90% of the DNA polymerase activity (30). As far as we know, none of the other HIV-1 RT mutants investigated here had been studied before, except for the E89G mutant.…”
Section: Resultsmentioning
confidence: 99%
“…This approach would allow "dissecting" between the clamp function and all other RT activities. Therefore, one of the suspected residues, Gln91, was not tested here, since it was already found that the Q91N HIV-1 RT mutation leads to a loss of Ͼ90% of the DNA polymerase activity (30). As far as we know, none of the other HIV-1 RT mutants investigated here had been studied before, except for the E89G mutant.…”
Section: Resultsmentioning
confidence: 99%